Recovering drought-tolerant traits from imported clones of Hevea brasiliensis through hybridization - Narayanan C; Mydin K K (Rubber Board Bulletin, 2015)
Clones of Hevea exhibit significantly variable response to seasonal factors which is particularly reflected in rubber yield during summer months. In view of the drastic change in climatological variables, development of clones amenable to drier conditions is need of the hour. Previous studies on performance of various clones under varied climates over the years had shown that clones like RRIC 52 and RRIC 104 introduced from Sri Lanka and few other imported clones were capable of performing well in terms of growth and yield, even under drier conditions. During 1993, as a part of breeding for drought tolerance, hybridization was carried out using above clones. After initial assessment for growth and yield at nursery stages, selections were subjected to further small scale evaluation. Sustainable yield of above hybrids during summer months, coupled with previous findings that these hybrids also possessed drought-tolerant traits based on physiological and biochemical studies, suggested that yield during summer months could be used as an indicator of drought tolerance in Hevea. Through hybridization, traits for drought tolerance were successfully recovered from imported clones, which established potential use of above drought tolerant clones as parents for conferring tolerance traits to off-springs to otherwise high-yielding clones of Hevea. Promising selections from the above breeding programme have already been identified as potential candidates for further long term evaluation in large scale as well as on-farm trials, in traditional and non-traditional regions experiencing drought phases, after which recommendations would be made for large-scale commercial planting.
Keywords: Annual yield; Drought tolerance; Girth; Summer depression; Summer yield